Quantitative ionization energies and work functions of aqueous solutions. Issue 42 (17th October 2016) - Olivieri, Giorgia; Goel, Alok; Kleibert, Armin; Cvetko, Dean; Brown, Matthew A.
Abstract : Redefining how ionization energies are determined from aqueous solutions: correcting for the electrochemical potential of the solution. Abstract : Despite the ubiquitous nature of aqueous solutions across the chemical, biological and environmental sciences our experimental understanding of their electronic structure is rudimentary—qualitative at best. One of the most basic and seemingly straightforward properties of aqueous solutions—ionization energies—are (qualitatively) tabulated at the water–air interface for a mere handful of solutes, and the manner in which these results are obtained assume the aqueous solutions behave like a gas in the photoelectron experiment (where the vacuum levels of the aqueous solution and of the photoelectron analyzer are equilibrated). Here we report the experimental measure of a sizeable offset ( ca. 0.6 eV) between the vacuum levels of an aqueous solution (0.05 M NaCl) and that of our photoelectron analyzer, indicating a breakdown of the gas-like vacuum level alignment assumption for the aqueous solution. By quantifying the vacuum level offset as a function of solution chemical composition our measurements enable, for the first time, quantitative determination of ionization energies in liquid solutions. These results reveal that the ionization energy of liquid water is not independent of the chemical composition of the solution as is usually inferred in the literature, a finding that has important ramifications as measured ionization energies are frequently used to validate theoretical models that posses the ability to provide microscopic insight not directly available by experiment. Finally, we derive the work function, or the electrochemical potential of the aqueous solution and show that it too varies with the chemical composition of the solution.